Pengaruh Sosialisasi Perpajakan Dan Modernisasi Sistem Administrasi Perpajakan Terhadap Kepatuhan Wajib Pajak Orang Pribadi Pada Kantor Pelayanan Pajak (Studi Kasus Di KPP Pratama Kediri) - Utama, Dafiq (Jurnal Sosial Teknologi, 2025)
This study has several objectives: to examine the effect of tax socialization on individual taxpayer compliance at KPP Pratama Kediri, to analyze the effect of modernization of the tax administration system on individual taxpayer compliance at KPP Pratama Kediri, and to investigate the combined effect of tax socialization and modernization of the tax administration system on individual taxpayer compliance at KPP Pratama Kediri. This research uses a quantitative method. The population consists of taxpayers’ data at KPP Pratama Kediri in 2024. The sampling technique is purposive sampling to select individual taxpayers according to criteria, with a sample size of 100 taxpayers calculated using the Slovin formula. Data collection is done by questionnaire, then instrument testing and data analysis are conducted using SPSS software. The results conclude that tax socialization can increase individual taxpayer compliance, modernization of the tax administration system can increase compliance, and both variables together also improve taxpayer compliance at KPP Pratama Kediri.